Equation #1
"y'''+y''=y+x^5" 1 STEP: Solve a homogeneous equation
"y'''+y''-y=0\\\\" We are looking for a solution in the form
"y(x)=e^{kx}\\longrightarrow\\,y''=k^2\\cdot e^{kx}\\,\\,\\,and\\,\\,\\,y'''=k^3\\cdot e^{kx}" Then,
"k^3\\cdot e^{kx}+k^2\\cdot e^{kx}-e^{kx}=0\\longrightarrow\\\\\nk^3+k^2-1=0" the cubic equation has three solutions: one real and two complex
"k_1=\\frac{1}{3}\\left(-1+\\sqrt[3]{\\frac{25}{2}-\\frac{3\\sqrt{69}}{2}}+\\sqrt[3]{\\frac{25+3\\sqrt{69}}{2}}\\right)\\\\[0.5cm]\nk_2=-\\frac{1}{3}-\\frac{1-i\\sqrt{3}}{6}\\left(\\sqrt[3]{\\frac{25}{2}-\\frac{3\\sqrt{69}}{2}}\\right)-\\frac{1+\ni\\sqrt{3}}{6}\\left(\\sqrt[3]{\\frac{25+3\\sqrt{69}}{2}}\\right)\\\\[0.5cm]\nk_3=-\\frac{1}{3}-\\frac{1+i\\sqrt{3}}{6}\\left(\\sqrt[3]{\\frac{25}{2}-\\frac{3\\sqrt{69}}{2}}\\right)-\\frac{1-\ni\\sqrt{3}}{6}\\left(\\sqrt[3]{\\frac{25+3\\sqrt{69}}{2}}\\right)\\\\[0.5cm]" Then,
"\\boxed{y(x)=C_1\\cdot e^{k_1x}+C_2\\cdot e^{k_2x}+C_3\\cdot e^{k_3x}-homogeneous\\,\\,\\,solution}" 2 STEP: Solve an Inhomogeneous Equation
We are looking for a solution in the form
"y(x)=Ax^5+Bx^4+Cx^3+Dx^2+Ex+F" Then,
"y''=20Ax^3+12Bx^2+6Cx+2D\\\\[0.3cm]\ny'''=60Ax^2+24Bx+6C" Substitute in the original equation
"60Ax^2+24Bx+6C+20Ax^3+12Bx^2+6Cx+2D=\\\\[0.3cm]\n=Ax^5+Bx^4+Cx^3+Dx^2+Ex+F+x^5\\longrightarrow\\\\[0.3cm]\n(A+1)x^5+Bx^4+(C-20A)x^3+\\\\[0.3cm]\n+(D-60A-12B)x^2+(E-24B-6C)x+(F-6C-2D)=0\\\\[0.3cm]\nA+1=0\\longrightarrow\\boxed{A=-1}\\\\[0.3cm]\n\\boxed{B=0}\\\\[0.3cm]\nC-20A=0\\longrightarrow\\boxed{C=-20}\\\\[0.3cm]\nD-60A-12B=0\\longrightarrow\\boxed{D=-60}\\\\[0.3cm]\nE-24B-6C=0\\longrightarrow\\boxed{E=-120}\\\\[0.3cm]\nF--6C-2D=0\\longrightarrow\\boxed{F=-240}\\\\[0.3cm]" Conclusion,
"y(x)=-x^5-20x^3-60x^2-120x-240-inhomogeneous\\,\\,\\,solution"
General conclusion:
"\\boxed{y(x)=C_1e^{k_1x}+C_2e^{k_2x}+C_3e^{k_3x}-x^5-20x^3-60x^2-120x-240}"
ANSWER
"y(x)=C_1e^{k_1x}+C_2e^{k_2x}+C_3e^{k_3x}-x^5-20x^3-60x^2-120x-240"
Equation #2:
"y\\cdot y''=y'+8x^3" 1 STEP: Solve a homogeneous equation
"y\\cdot y''=y'\\longrightarrow y''=\\frac{y'}{y}\\longrightarrow\\\\[0.3cm]\n\\frac{d}{dx}\\left(y'\\right)=\\frac{d}{dx}\\left(\\ln(y)\\right)\\longrightarrow y'=\\ln(Cy)\\longrightarrow\\\\[0.3cm]\n\\frac{dy}{dx}=\\ln(Cy)\\longrightarrow\\int\\frac{dy}{\\ln(Cy)}=\\int1dx" Since
"\\int\\frac{dy}{\\ln(Cy)} \\,is\\, the\\,integral\\,logarithm, not\\,an\\,elementary\\,function"
This means that we can’t write down the general solution of this equation in the usual elementary functions. The only thing we CAN write is
"\\boxed{li(y)=x+C}" More information: https://en.wikipedia.org/wiki/Logarithmic_integral_function
Comments
Leave a comment